Educação física no CIEJA Sapopemba: desafios e possibilidades - Fernandes, Wellington Camargo (2020)
This investigation, which is linked to the line of research and intervention on Educational Management (LIPIGES) of the Professional Master's program in Management and Educational Practices (PROGEPE) at Nove de Julho University (UNINOVE), aims at discussing the challenges and possibilities of Physical Education practice in the context of Youth and Adult Education (EJA), having as object of study the reality experienced by the researcher, at the Integrated Center for Youth and Adult Education (CIEJA) at the Sapopemba unit, linked to the Municipal Education Network of São Paulo. The problematizing questions that motivated and directed the development of this research were: What are the weaknesses and potentialities of Physical Education teaching at CIEJA Sapopemba, considering that this curricular component becomes invisible in this context? What are the possibilities of teaching Physical Education in this scenario? What value does this component carry in the EJA curriculum? The main objective was to identify the dimensions, the weaknesses and the potentialities of the practice of Physical Education directed to the Education of Youth and Adults. Specific objectives were listed as: (1) Recognize the importance of Physical Education for EJA; (2) Reflect on the urgent continuing training for Physical Education teachers to work at EJA; (3) Carry out a critical self-analysis of the Physical Education methodology and teaching plans at CIEJA Sapopemba. The methodology that was used in this exploratory investigation, which was configured as a case study with a qualitative approach, involved bibliographic research, which started from an archive of theses and dissertations on the researched theme and documentary analysis of the official guidelines on this teaching modality and also the analysis of the teaching plans proposed for this context. The Theoretical contribution was supported by the authors: Paulo Freire, Maria Clara Di Pierro, Sérgio Haddad, among other important authors that are part of our bibliography. The results obtained indicate the need for a curriculum that is in fact participatory to bridge the gap between what is proposed and what is actually accomplished in class. The fragmentation and isolation of the teaching plans that would need an effective cultural action between teachers, managers, and students became evident and also the urgency of continuing education for Physical Education teachers who work at EJA. As an intervention proposal, we proposed in the final remarks, a decalogue that we believe may be useful for teachers who work with Physical Education at EJA.